Immediate and delayed solubility of mineral trioxide aggregate and Portland cement - Augusto Bodanezi; Nara Carvalho; Daniela Silva; Norberti Bernardineli; Clovis Monteiro Bramante; Roberto Brandão Garcia; Ivaldo Gomes de Moraes (University of São Paulo, 2008)
This study investigated the solubility of mineral trioxide aggregate (MTA) and Portland cement since its mixture until 672 hours, by means of two complimentary methods. Metal ring molds filled with the cements were covered with distilled water and, at each experimental time (3, 24, 72, 168, 336 and 672 hours), were weighed as soon as the plates in which the samples have been placed. Empty rings served as the control group (n=8). Mean weight gain and loss was determined and analyzed statistically by two-way ANOVA and Tukey's test for all pairwise comparisons. Only Portland cement showed less than 3% weight loss through 24 hours. Detached MTA residues were heavier than those of Portland cement over the 3 to 168 hours. The weight of MTA rings increased more than that of Portland rings within 672 hours (p=0.05). The findings of the present study indicate that, in an aqueous environment MTA is more soluble than Portland cement and exceeds the maximum weight loss considered acceptable by ISO 6876 standard (2001).